Origin And Development Of Pancamahabhoota Theory In Applied Ayurveda - Nandeesh, V d J; Praveen , Vd Kumar B (International Research Journal of Ayurveda & Yoga, 2020)
Ayurveda is a holistic science which is considered to be anadi in origin. It is logical to claim its existence since the appearance of life on earth. Living in harmony was the major factor which helped man to know the nature in a subtle way. People were dependent on nature for food and shelter. They accustomed to a healthy lifestyle probably through multiple trial and errors. Owing to the intellectual abilities and keen observational skills, ancient scholars explored the universe in relation to human body for promoting health. During the process, various theories were proposed like pancamahabhoota siddhanta and pinda brahmanda nyaya. Subsequently, these theories further underwent through various stages of development and became base for all the basic principles of Ayurveda. In this work, probable method of origin of pancamahabhoota siddhanta is explored retrospectively and various subsequent doctrines derived from this theory are explored from clinical point of view.